Prolonged dialysis duration is associated with graft failure and mortality after kidney transplantation: results from the French transplant database. Issue 3 (22nd March 2018) - Prezelin-Reydit, Mathilde; Combe, Christian; Harambat, Jérôme; Jacquelinet, Christian; Merville, Pierre; Couzi, Lionel; Leffondré, Karen
Abstract: Background: Kidney transplantation (KT) is the treatment of choice for end-stage renal disease. Preemptive KT (PKT) should be considered when glomerular filtration rate is <15 mL/min/1.73 m 2 but European reports on the results of PKT and the effect of pretransplant dialysis are scarce. Methods: We analysed all first kidney-only transplants performed in adults in France between 2002 and 2012. A Cox multivariable model was used to investigate the association of PKT and of pretransplant dialysis time with the hazard of graft failure defined as death, return to dialysis or retransplant, whichever occurred first. Results: We included 22 345 patients, with a mean ± SD age at KT of 50.5 ± 13.4 years; 61.9% were men and 3112 (14.0%) received a PKT. Median time of follow-up was 4.7 years. Graft failure occurred in 4952 patients up to 31 December 2013. After adjustment for recipients' age and sex, primary kidney disease, donor type (living or deceased donor, expanded criteria donor), HLA mismatches, cold ischaemia time, centre and year of transplantation, PKT was associated with a decreased hazard of graft failure when compared with pretransplant dialysis [hazard ratio (HR) 0.57; 95% confidence interval (CI) 0.51–0.63], whatever the duration of dialysis, even in the first 6 months. The effect of PKT on the hazard of graft failure was stronger in living kidney donors (HR 0.32; 95% CI 0.19–0.55). Conclusions: In France, PKT was associated with a lower risk of graft failure than KT performed after the initiation of dialysis, whatever the duration of dialysis.